Human Case of Severe Fever with Thrombocytopenia Syndrome Virus Infection, Taiwan, 2019 - Peng, Shih-Huan; Yang, Su-Lin; Tang, Shih-En; Wang, Tzy-Chen; Hsu, Tung-Chien; Su, Chien-Ling; Chen, Meng-Yu; Shimojima, Masayuki; Yoshikawa, Tomoki; Shu, Pei-Yun (Emerging infectious diseases, 2020)
We report on a 70-year-old man with fever, leukopenia, thrombocytopenia, vomiting, malaise, dyspnea, and consciousness disturbance who was infected with severe fever with thrombocytopenia syndrome virus in northern Taiwan, 2019. This autochthonous case was confirmed by reverse transcription PCR, virus isolation, and genomic sequencing.